1994
DOI: 10.1029/93wr02948
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of time domain reflectometry waveforms: 1. Measurement of the complex dielectric permittivity of soils

Abstract: The S11 scatter function of a coaxial probe in the frequency domain is shown to be an accurate model for predicting waveforms of a seven‐wire coaxial probe in the time domain. Reproducibility of discrete Fourier analyses carried out on waveforms measured with the Tektronix 1502b cable tester (Tektronix, Incorporated, Beaverton, Oregon) indicated a frequency band width ranging from 20 kHz to approximately 1.5 GHz. The frequency dependent complex dielectric permittivity can be calculated from measured waveforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
173
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 20 publications
2
173
1
2
Order By: Relevance
“…This is quite low compared to the K values measured up to 4 MHz frequency ( Figure 5). The TDR instrument (TDR1502C) uses a step pulse that contains frequencies from 20 kHz to 1.5 GHz [Heimovaara, 1994]. The dielectric constant of the epoxy-ceramic appears to be lower than expected at these higher frequencies.…”
Section: Results and Discussion Of Effect Of High Dielectric Coatingmentioning
confidence: 99%
“…This is quite low compared to the K values measured up to 4 MHz frequency ( Figure 5). The TDR instrument (TDR1502C) uses a step pulse that contains frequencies from 20 kHz to 1.5 GHz [Heimovaara, 1994]. The dielectric constant of the epoxy-ceramic appears to be lower than expected at these higher frequencies.…”
Section: Results and Discussion Of Effect Of High Dielectric Coatingmentioning
confidence: 99%
“…The sampling interval is determined by the frequency bandwidth of the TDR measurement system. For the Tektronix 1502B cable tester it was determined to be from dc up to 1.5 GHz [Heimovaara, 1994]. The sample length is selected such that a steady state is reached at the end of the TDR waveform, which means the waveform should achieve a constant value.…”
mentioning
confidence: 99%
“…Extensive reviews of TDR applied to soil moisture determination can be found in [55] and [54]. Frequency domain reflectometry (FDR) uses the same principle as TDR, but analyzes the reflected waveform in the frequency domain, enabling the determination of frequency dependent complex dielectric permittivity [56]. This facilitates the separation of probe response and soil response and enables better extraction of useful information [57].…”
Section: Time Domain Reflectometrymentioning
confidence: 99%